2018
DOI: 10.1007/s12289-018-01458-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct usage of the wire drawing process for large strain parameter identification

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Cetlin suggested a parabolic equation for the distribution of strain using an experiment for establishing the relationship between hardness and strain [10]. In Figure 11, it can be observed that the distribution of strain is similar not only to that of Cetlin’s research but also to that of Vent’s research using FEA [9].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Cetlin suggested a parabolic equation for the distribution of strain using an experiment for establishing the relationship between hardness and strain [10]. In Figure 11, it can be observed that the distribution of strain is similar not only to that of Cetlin’s research but also to that of Vent’s research using FEA [9].…”
Section: Resultsmentioning
confidence: 59%
“…Additionally, Celentano et al predicted the distribution of effective strain from the center to the surface of a steel wire based on an FEA [8]. Venet et al used an FEA to plot the effective strain of a multi-pass steel wire drawing process [9] and observed that the strain distribution showed no sensitivity to the work hardening coefficient of the wire material. Cetlin evaluated the deformation within the drawn aluminum wire cross section using the hardness profile method in two-pass drawing [10].…”
Section: Introductionmentioning
confidence: 99%
“…The compression test’s strain rate of the three specimens was 0.1 1/s. The isotropic hardening behavior of the material was modeled using the Swift approach [ 19 ]. Figure 4 shows the flow curve and the extrapolation for higher plastic strain.…”
Section: Methodsmentioning
confidence: 99%
“…The Swift-Voce combined law was used as it is repeatedly identified in the literature as one of the most adequate isotropic hardening law to describe large strain hardening behavior of sheet metals, in particular steels [12], [17].…”
Section: Swift-voce Isotropic Hardeningmentioning
confidence: 99%